Van der Waals density functional study of the structural and electronic properties of La-doped phenanthrene - Yan, Xun-Wang; Huang, Zhongbing; Lin, Hai-Qing (The Journal of chemical physics, 2013)
By the first principle calculations based on the van der Waals density functional theory, we study the crystal structures and electronic properties of La-doped phenanthrene. Two stable atomic geometries of La₁phenanthrene are obtained by relaxation of atomic positions from various initial structures. The structure-I is a metal with two energy bands crossing the Fermi level, while the structure-II displays a semiconducting state with an energy gap of 0.15 eV, which has an energy gain of 0.42 eV per unit cell compared to the structure-I. The most striking feature of La₁phenanthrene is that La 5d electrons make a significant contribution to the total density of state around the Fermi level, which is distinct from potassium doped phenanthrene and picene. Our findings provide an important foundation for the understanding of superconductivity in La-doped phenanthrene.